Peranan Strategi Pemasaran Dalam Upaya Meningkatkan Penjualan Jasa Asuransi pada PT Asuransi Umum Bumiputera Muda 1967 Medan - Sakinah Sakinah; Nur Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This review is expected to be ableto dissect the procedure of promotion work through the combination of 7Ps implemented by PT. General Insurance Bumiputera Muda 1967 Medan is now ready to compete in the field, this exam uses a fascinating exploration technique. This inspection was led by an organization engaged in the protection sector, namely PT. Bumiputera Muda General Insurance 1967 Medan. The methods of collecting information from this examination are (perception), documentation and meetings. Information obtained from the consequences of essential information and optional information. The information checking strategy used is an enlightening investigation that clarifies the actual conditions that occur substantially and significantly and explains exploratory information. The side effect of this expressive review is that the agreement is shaky and will often diminish with each passing year at PT. Bumiputera Muda 1967 General Insurance Medan was caused by the absence of the largest 7P advertising mix job vacancy applied by PT. Bumiputera Muda General Insurance 1967 Medan. The job of assisting the promotion procedure through the 7P advertising blend carried out by PT. Bumiputera Muda 1967 General Insurance Medan from the part (goods) offered to be competitive in search and very good, in terms of value it can compete in search, part of the circulation channel (place) is still not ideal and there are still weaknesses, part of progress (forward) ) is still not ideal and still uses the old strategy, the individual point of view is very large, the cycle perspective is sufficient, the point of view of tangible evidence is still poor in times of serious market competition.